2022
DOI: 10.3390/nu14081675
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Water-Soluble Carotenoid-Rich Extract of Cordyceps militaris against Light-Evoked Functional Vision Deterioration in Mice

Abstract: Light-evoked retinal photodamage is considered an important factor contributing to functional vision deterioration and can even lead to light maculopathy or dry age-related macular degeneration. Loss of visual acuity (VA) and visual contrast sensitivity function (VCSF) are the major symptoms of retinal degenerative diseases. Cordyceps militaris is a carotenoid-rich Chinese medicinal fungus with antioxidant, anti-inflammatory, and immunomodulatory functions. C. militaris extract is a natural substance, and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Carotenoids have also exhibited great efficacy in the prevention of vision loss and retinal damage. Chen et al (2022) conducted an in vivo study on albino mice and reported that aqueous carotenoid extract of Cordyceps militaris protected the neural retinal tissue by ceasing light‐induced cell death.…”
Section: Sources Of Plant Pigments and Benefits To Mankindmentioning
confidence: 99%
“…Carotenoids have also exhibited great efficacy in the prevention of vision loss and retinal damage. Chen et al (2022) conducted an in vivo study on albino mice and reported that aqueous carotenoid extract of Cordyceps militaris protected the neural retinal tissue by ceasing light‐induced cell death.…”
Section: Sources Of Plant Pigments and Benefits To Mankindmentioning
confidence: 99%
“…Similarly, medicinal fungi can also exert antioxidant effects against UVA radiation. Ganoderma lucidum extract can resist photodamage by regulating the cell cycle and decreasing the number of apoptotic cells [65,66]. However, there is relatively little research on A. blazei Murill.…”
Section: Discussionmentioning
confidence: 99%
“…These nutrients have been related to better neuronal plasticity, and reduced gliosis and oxidative stress, and appear to maintain neurogenesis and blood-brain barrier integrity in in vitro studies and animal models. [50][51][52] Further, the MIND diet pattern also limits high saturated fat, high-sugar foods, and red and processed meats. Saturated fats and sugars may induce neuroinflammation by mediating mitrogen-activated protein kinase and nuclear factor kappa B signaling pathways, negatively impacting BDNF pathways and increasing blood-brain barrier permeability in the hippocampus causing synaptic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MIND diet is also rich in other essential nutrients, such as long‐chain omega‐3 fatty acids from fish and nuts; B vitamins from vegetables and whole grains; and vitamin K and lutein from green leafy vegetables. These nutrients have been related to better neuronal plasticity, and reduced gliosis and oxidative stress, and appear to maintain neurogenesis and blood–brain barrier integrity in in vitro studies and animal models 50–52 . Further, the MIND diet pattern also limits high saturated fat, high‐sugar foods, and red and processed meats.…”
Section: Discussionmentioning
confidence: 99%